THE INVESTIGATION OF CLASSROOM TEACHERS' ATTITUDES TOWARDS THE VALUE EDUCATION IN THE TERM OF VARIOUS VARIABLES - Cihat YAŞAROĞLU (Fırat University, 2019)
This study has been done to determine the claassroom teachers attitudes towards the values education being implemented at schoools. The first course circular that published by the Ministry of Education in 2010 became a turning point in term of works of values education to be official and dissemination. But it is a known fact that the teacher is a key role for a programme adoption or being implemented successfully. For this purpose, the requirement of classroom teacher attitudes towards values education has born. It should be kept in mind that the taechers who have positive attitudes towards values educations will it implement more effectively. In order to determine the diffenrentiation status of classroom teachers’ attitudes related to values education and this attitude in terms of several variables have been developed and implemented by researcher with " Values Education Attitude Scale " that consists of 25 items. This study is a screening model and of a descriptive nature. The study universe is composed of the classroom teachers who work at primary school in Bingöl. All of the teachers have been reached and the data collection tool was distributed on a voluntary basis. Accordingly, 162 teachers completed the scale and provided feedback. Four of these scales were eleminated at the first analysis as they were filled incorrectly or incompletely. So the analysis has done on the scales that filled by the 158 teachers. The scale 's internal reliability coefficient was calculated by Cronbach alpha and found as 92. In the analysis of data; percentage and frequency were used in personal information. The distribution of the scale scores were examined and it was determined that the distribution wasn’t parametric. Therefore, the Mann-Whitney U and the Kruskal-Wallis tests which are non-parametric statistical analysis techniques were used to test difference of the scores obtained from the scale in the term of several variables. The significance level was taken .05 in all comparisons. According to the analysis, the classroom teachers attitudes’ towards value education were positive, the scores of attitude neither changed by the gender nor by the variablity of the class they teach, but got significantly differing conclusions for the seniority and variable type of the school graduated from. Based on these findings, various suggestions have been made.